2005
DOI: 10.1515/bc.2005.055
|View full text |Cite
|
Sign up to set email alerts
|

Ultraspiracle promotes the nuclear localization of ecdysteroid receptor in mammalian cells

Abstract: The heterodimer consisting of ecdysteroid receptor (EcR) and ultraspiracle (USP), both of which are members of the nuclear receptor superfamily, is considered to be the functional ecdysteroid receptor. Here we analyzed the subcellular distribution of EcR and USP fused to fluorescent proteins. The experiments were carried out in mammalian COS-7, CHO-K1 and HeLa cells to facilitate investigation of the subcellular trafficking of EcR and USP in the absence of endogenous expression of these two receptors. The dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 41 publications
7
41
0
Order By: Relevance
“…Therefore, earlier we had analyzed the subcellular trafficking of the EcRB1 isoform and Usp in mammalian cells (CHO-K1, COS-7 and HeLa) which are routinely used for EcR/Usp heterologous studies (Gwozdz et al, 2007;Nieva et al, 2005). The experiments showed that the intracellular distribution of EcR was dependent on time and cell type.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, earlier we had analyzed the subcellular trafficking of the EcRB1 isoform and Usp in mammalian cells (CHO-K1, COS-7 and HeLa) which are routinely used for EcR/Usp heterologous studies (Gwozdz et al, 2007;Nieva et al, 2005). The experiments showed that the intracellular distribution of EcR was dependent on time and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account current data about nuclear receptors (Laudet and Gronemeyer, 2002), including our recently published data (Gwozdz et al, 2007;Nieva et al, 2005), it is reasonable to assume that the EcR/Usp complexes are formed due to the direct interaction between the ligand binding Page 15 of 27 A c c e p t e d M a n u s c r i p t 15 domains (LBDs) of both receptors. However, the interaction that brings together EcR and Usp and thus localizes them in the nucleus, may not be a direct interaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations